Dampak Multibahasa terhadap Peluang Karir Mahasiswa Pariwisata di STIEPAR - Oktian Frista Ramadini; Josefa Francesca Sella (Tamasya : Jurnal Pariwisata Indonesia, 2025)
In the era of globalization, the tourism sector is experiencing rapid growth and requires a workforce that not only has technical skills, but also intercultural communication abilities. The ability to master more than one language or multilingualism is a crucial skill for tourism students to compete in an increasingly competitive job market. The purpose of this study was to analyze the role of multilingualism in expanding career opportunities for tourism students at STIEPAR. The method applied was a survey using a questionnaire addressed to tourism students. The results of the study showed that all respondents (100%) considered the importance of foreign language skills in the world of tourism. Many students believe that their multilingual ability increases their competitiveness and helps prepare them to face the work challenges that exist in the global industry. However, there are challenges such as lack of opportunities for hands-on practice and adequate language learning facilities. The results of this study emphasize the importance of strengthening the foreign language curriculum in tourism education institutions, as well as the need for policy support and external collaboration to create a learning atmosphere that is active, relevant, and in line with industry demands.